Papua New Guinea : Background Material. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This Background Material paper describes developments in the mineral sector of Papua New Guinea during the 1990s. It examines causes and implications of the buildup in fiscal arrears. The paper highlights that one of the notable developments in 1994 was the emergence of large fiscal arrears, which had important effects on monetary and external developments during the second half of 1994 and early 1995. The paper also provides background information on the causes of these arrears and the actions taken by the authorities to settle them.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet